Leading Change: Exploring the Role of Women's Political Leadership in Driving Effective Development in Parangloe Village - Arif, Achmad Fadil; Mustari, Nuryanti; Harakan, Ahmad (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2023)
This study aims to analyze the influence of women's political leadership styles on the effectiveness of development in Parangloe Village, Bantaeng Regency. The research design employed is a quantitative method, utilizing a questionnaire as the main instrument. The population under study comprises the residents of Parangloe Village, Bantaeng Regency, and the sample size determination utilized the Slovin technique due to the large and challenging-to-reach population. The study selected 90 respondents as samples. Data collection methods involved both observation and the distribution of questionnaires. The data analysis technique employed in this study is regression analysis. Validity and reliability of the data were ensured through validity testing. The findings of this study indicate that the influence of women's political leadership styles on the effectiveness of development in Parangloe Village, Bantaeng Regency, is positive. This is supported by the average score of 168.8 or 84%, suggesting a very favorable position for the impact of women's leadership style. Furthermore, the research also reveals a positive effect of women's leadership on development in Parangloe Village, Bantaeng Regency, with a percentage of 69.1%, while the remaining 30.9% is attributed to other factors.